A single high-fat meal provokes pathological erythrocyte remodeling and increases myeloperoxidase levels: implications for acute coronary syndrome. (October 2018) - Benson, Tyler; Weintraub, Neal; Kim, Ha; Seigler, Nichole; Kumar, Sanjiv; Pye, Jonathan; Horimatsu, Tetsuo; Pellenberg, Rod; Stepp, David; Lucas, Rudolf; Bogdanov, Vladimir; Litwin, Sheldon; et al.
Abstract High-fat meal (HFM) consumption can produce acute lipemia and trigger myocardial infarction in patients with atherosclerosis, but the mechanisms are poorly understood. Erythrocytes (red blood cells, RBCs) intimately interact with inflammatory cells and blood vessels and play a complex role in regulating vascular function. Chronic high-fat feeding in mice induces pathological RBC remodeling, suggesting a novel link between HFM, RBCs, and vascular dysfunction. However, whether acute HFM can induce RBC remodeling in humans is unknown. Ten healthy individuals were subjected to biochemical testing and assessment of endothelial-dependent flow-mediated dilation (FMD) before and after a single HFM or iso-caloric meal (ICM). Following the HFM, triglyceride, cholesterol, and free fatty acid levels were all significantly increased, in conjunction with impaired post-prandial FMD. Additionally, peripheral blood smears demonstrated microcytes, remodeled RBCs, and fatty monocytes. Increased intracellular ROS and nitration of protein band 3 was detected in RBCs following the HFM. The HFM elevated plasma and RBC-bound myeloperoxidase (MPO), which was associated with impaired FMD and oxidation of HDL. Monocytic cells exposed to lipid in vitro released MPO, while porcine coronary arteries exposed to fatty acids ex vivo took up MPO. We demonstrate in humans that a single HFM induces pathological RBC remodeling and concurrently elevates MPO, which can potentially enter the blood vessel wall to trigger oxidative stress and destabilize vulnerable plaques. These novel findings may have implications for the short-term risk of HFM consumption and alimentary lipemia in patients with atherosclerosis. A single high fat meal can induce pathological red blood cell (RBC) remodeling and oxidative stress, in conjunction with elevations in plasma, RBC-bound myeloperoxidase (MPO) and MPO-mediated high-density lipoprotein oxidation. These findings demonstrate that consumption of heavy meals enriched in fat may promote destabilization of vulnerable plaques leading to acute myocardial infarction.